Approximate Solution of Time-Fractional Helmholtz and Coupled Helmholtz Equations - Bayrak, Mine Aylin; Tetik, Semiha (Communications in Mathematics and Applications, 2020)
The approximate analytical solution of the time-fractional Helmholtz and coupled Helmholtz equations have been acquired successfully via Residual Power Series Method (RPSM). The approximate solutions obtained by RPSM are compared with the exact solutions through different graphics and tables. The fractional derivatives are described in the Caputo sense. The numerical results demonstrate that the new method is quite accurate and readily implemented.